An efficient technique for solving the scheduling of appliances in smart-homes - Hendrickx, Julien M.; Jungers, Raphael M.; Vankeerberghen, Guillaume; Wolsey, Laurence A. (2014 American Control Conference, 2014)
In the development of the electricity grid, Demand Response is a current subject of research for reasons of robustness, efficiency and renewable energy integration. Among the aspects of Demand Response, dynamic pricing is critical, and real-time pricing is a favored way of implementing it. The efficiency of such methods would however rely crucially on the ability and willingness of the end-user to react to varying prices. For this reason, we look at the problem of automatically scheduling the appliances that a user needs to run when the energy price is sent by the provider. We propose a discrete-time formulation for this problem, show how it can be solved by a minimum cut algorithm and compare it with previously proposed techniques. Compared to an exact method requiring a mixed integer programming solver, our approach produces solutions very close to optimal in shorter running times and does not require proprietary software.